Judicial Considerations in Child Marriage Dispensations: An Empirical Study of the Gorontalo Religious Court - Insani, Nur; Beddu, Sumiyati; Rahman, Rahmawati; Arpin, Arpin; Samuri, Mohd Al Adib (IAIN Manado, 2024)
This research aims to determine the judge's considerations in carrying out his juridical function to adjudicate cases, whether they align with legal principles governing marriage and protecting children's rights, and how social stigma influences the judge's decision-making process in many instances. Interviews were conducted directly to create effective and efficient discussions to collect the primary data. In addition, data was obtained through literature and research studies, including regulations, documents, and related books. This paper examines a case study concerning a judge's decision to grant dispensation to a married couple not yet of legal age due to a request for parental guardianship submitted to the Gorontalo Religious Court in decision Number 10/Pdt.P/2021/PA. The findings show that the convergence of various legal aspects, cultural values, and social norms can influence judges' considerations in determining child marriage dispensations. The issue of child marriage in Indonesia is complex and needs serious attention. A legal framework must support objective legal principles, take into account the needs and interests of all parties, and overcome social stigma against child marriage.